Statistical Learning in a Bilingual Environment - Tsui, Sin Mei (Université d'Ottawa / University of Ottawa, 2018)
Statistical learning refers to the ability to track regular patterns in sensory input from ambient environments. This learning mechanism can exploit a wide range of statistical structures (e.g., frequency, distribution, and co-occurrence probability). Given its regularities and hierarchical structures, language is essentially a pattern-based system and therefore researchers have argued that statistical learning is fundamental to language acquisition (e.g., Saffran, 2003). Indeed, young infants and adults can find words in artificial languages by tracking syllable co-occurrence probabilities and extracting words on that basis (e.g., Saffran. Aslin & Newport, 1996a). However, prior studies have mainly focused on whether learners can statistically segment words from a single language; whether learners can segment words from two artificial languages remains largely unknown. Given that the majority of the global population is bilingual (Grosjean, 2010), it is necessary to study whether learners can make use of the statistical learning mechanism to segment words from two language inputs, which is the focus of this thesis. I examined adult and infant learners to answer three questions: (i) Can learners make use of French and English phonetic cues within a single individual’s speech to segment words successfully from two languages?; 2) Do bilinguals outperform monolinguals?; and 3) Do specific factors, such as cognitive ability or bilingual experience, underlie any potential bilingual advantage in word segmentation across two languages? In Study 1, adult learners generally could make use of French and English phonetic cues to segment words from two overlapping artificial languages. Importantly, simultaneous bilinguals who learned French and English since birth segmented more correct words in comparison to monolinguals, multilinguals, and sequential French-English bilinguals. Early bilingual experience may lead learners to be more flexible when processing information in new environments and/or they are more sensitive to subtle cues that mark the changes of language inputs. Further, individuals’ cognitive abilities were not related to learners’ segmentation performance, suggesting that the observed simultaneous bilingual segmentation advantage is not related any bilingual cognitive advantages (Bialystok, Craik, & Luk, 2012). In Study 2, I tested 9.5-month-olds, who are currently discovering words in their natural environment, in an infant version of the adult task. Surprisingly, monolingual, but not bilingual, infants successfully used French and English phonetic cues to segment words from two languages. The observed difference in segmentation may be related to how infant process native and non-native phonetic cues, as the French phonetic cues are non-native to monolingual infants but are native to bilingual infants. Finally, the observed difference in segmentation ability was again not driven by cognitive skills. In sum, current thesis provides evidence that both adults and infants can make use of phonetic cues to statistically segment words from two languages. The implications of why early bilingualism plays a role in determining learners’ segmentation ability are discussed.
Keywords: Psychology; Statistical learning; Word segmentation; Bilingualism